FROM CHARISMA TO LEGITIMACY: VILLAGE KYAI LEADERSHIP STRATEGIES IN MAINTAINING RELIGIOUS AUTHORITY ACROSS GENERATIONS - Shodiqul Anwar; Hefniy Hefniy; Bayyina Sapuding (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Motivation to learn is a crucial factor in shaping students' academic achievement. However, dependence on a digital lifestyle, including online games, can disrupt students' sleep quality and focus on learning. This study aimed to examine the effects of online gaming intensity and sleep quality on students’ learning motivation. A quantitative approach was employed using multiple linear regression analysis, involving 110 active undergraduate students from the Faculty of Medicine, Udayana University. The results showed a significance value of 0.000 (p < 0.05) with a coefficient of determination (R²) of 0.804. This indicates that online gaming intensity and sleep quality together significantly influence learning motivation, accounting for 80.4% of the variance. The standardized beta coefficient for online gaming intensity was -0.757 (p = 0.000), indicating a strong negative effect on learning motivation. Similarly, the standardized beta coefficient for sleep quality was -0.191 (p = 0.001), indicating a significant negative impact as well. In conclusion, lower online gaming intensity and better sleep quality are associated with higher learning motivation among students.